A organização escolar em ciclos na rede municipal de Araraquara - 2001 a 2005 - Fraiz, Rosana Cristina Carvalho (2006)
The school organization in series predominates in Brazil since 19º century and still shows its power because it´s solidified in teachers, parents and students conception. Different experiences have been introduced since 60´s decade on the attempt to break the school succession. On the 90´s decade, emerge proposals of modification in the school periods and places of which centre becomes the cycles´s formation. To describe and analyze the introduction of the school organization base don development cycles on the Araraquara´s municipal education system is necessary to retake some previous experiences and the debates that go along with the cycles and continued progression, making evident that the cycles system conflicts with the school culture strongly based on the organization in series. The new way of organization presupposes changes in the education-learning conception, the evaluation method and the proper school, showing that punctual changes isn t enough. The way how this introduction has been done in Araraquara makes evident that educational public politics depends on their real comprehension and education of their protagonists: teachers, parents and students. On the attempt of modifying the school organization present problems like a relative unsure about the school proposes and missions and the resignificance process of the teacher s role can be added to de discussion. The reflection point to some paths and sures. Paths that indicates the essential participation of whole community on the previous discussion about the introduction of the new education system, constant evaluation of the process and education to create the reflection of the theory and practice. Sures that education changes has to be understand like a transformation of ideas and practice and it can t happen suddenly and in a linear way, but it´s possible to create an another school.